Perspectives and challenges for higher education in Latin America and the Caribbean: Interview with Roberto Leher, Rector of the Federal University of Rio de Janeiro, with comments made by Mário Luiz Neves de Azevedo, from the State University of Maringá - Fernanda Geremias Leal; Roberto Leher; Mário Luiz Luiz Neves De Azevedo (Arizona State University, 2018)
An interview with Professor Roberto Leher, Rector of the largest federal public university in Brazil, the Federal University of Rio de Janeiro (UFRJ), on the situation of higher education in the country and in Latin America and the Caribbean. The interview addresses the preparation of Asociación de Universidades Grupo Montevideo (AUGM), created in 1990 and composed by 35 public universities from Argentina, Bolivia, Brazil, Chile, Paraguay and Uruguay, for the III Regional Conference for Higher Education (CRES), held in Cordoba, Argentina, in June 2018. The interview addresses, among other aspects, higher education as a public good and fundamental human social and individual right; the commodification of the sector in Latin America; the influence of international organizations in the directions of higher education around the world; the advances of science and the challenges in the development of the countries of the region; the importance of CRES for the future of the university, as well as the role of student participation and mobilization in this scenario. At the end of the interview, there is an analysis with comments made by Professor Mario Luiz Neves de Azevedo, researcher of the field in Brazil.